The The Effect of Digital Picture Series on Students’ Writing Procedure Text at Tenth Grade of SMAN 1 Kramatwatu - Mawaddah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
This study aimed to determine the effect of digital picture series as media on the writing skills of procedure texts of class X students of SMAN 1 Kramatwatu. This study uses a quasi-experimental research method with a nonequivalent control group design. The population in this study were all students of class X SMAN 1 Kramatwatu totaling 314 students with two classes as samples, namely class X4 totaling 40 students as the experimental class and class X1 totaling 40 students as the control class. The data collection technique used was a procedure text writing test. To test the pretest hypothesis, the t-test was used and the results of the study showed a calculated t value = 0.541 and t table = 2.000 which means there is no difference between the experimental class and the control class. To test the posttest hypothesis, the results of the t-test showed a calculated t value = 12.662 and t table = 2.000 which showed a significant difference between the experimental class and the control class after the teaching and learning process was carried out. This shows that the use of digital picture series media has a significant effect on the writing skills of class X students of SMAN 1 Kramatwatu.